EXPLORING STUDENTS’ PERCEPTIONS OF ARTIFICIAL INTELLIGENCE IN THE WRITING PROCESS - Ananda, Desta; Wulandari, Fitri; Khotimah, Khusnul; Safitri, Anida Faradila (Jurnal Smart, 2025)
This study examines students’ perceptions of the use of artificial intelligence (AI) across stages of the academic writing process. A mixed-methods approach with a sequential explanatory design was applied. Data were obtained from questionnaires administered to 58 students in the English Education Study Program at Muhammadiyah University Pringsewu and supported by semi-structured interviews. The results indicate that students generally perceive AI as supportive in planning, drafting, revising, and editing, particularly in organizing ideas, improving language accuracy, and enhancing writing quality. When used ethically, AI was also reported to increase students’ confidence and efficiency in academic writing.